Fostering Collaborative Learning through YouTube and WhatsApp: Insights from EFL Reading Comprehension Courses - Adi Isma; Putu Wahyu Sudewi; Andi Mega Januarti Putri (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
The integration of social media platforms in EFL reading instruction remains underexplored, particularly regarding their combined pedagogical potential for enhancing collaborative learning experiences. This study investigates how YouTube and WhatsApp function as complementary collaborative learning tools in EFL reading courses, addressing the gap in research on their synergistic effects on reading comprehension and peer interaction. Using a sequential explanatory mixed-methods approach, data were collected from 100 third-semester students through questionnaires, with 40 randomly selected participants providing reflective journals. The research examined students' perceptions of these platforms' effectiveness in supporting collaborative reading activities and identified correlations between platform use and learning engagement. The findings indicate that students perceived both platforms positively, with YouTube presentations supporting comprehension of reading materials and WhatsApp discussions fostering collaborative engagement. However, challenges such as limited interaction during video presentations, technological barriers, and message overload in group chats were also reported. Thematic analysis further revealed five key themes: learning engagement, collaborative experiences, online learning challenges, platform benefits, and improvement suggestions. The study contributes practical insights for optimizing social media integration in EFL reading instruction through structured engagement strategies, balanced participation guidelines, and blended learning approaches that combine synchronous and asynchronous collaborative reading activities.